Pension Plan (JHT) by the Government in the Manpower Sector Based on the Concept of the State of Law in the City of Tangerang - Yusmedi Yusuf; Annie Myranika; Sofiatul Karimah; Muhammad Rizqi Fadhlillah (Faculty of Law, Universitas Pekalongan, 2023)
The government in the field of manpower has issued a new regulation regarding Pension Plan (JHT) for workers/laborers when they enter retirement age, experience total disability and die. In the new regulation issued by the Minister of Manpower, it has changed the application of JHT for workers to obtain the benefits of JHT payments after reaching the age of 56 (fifty six) years. JHT which is issued based on the Regulation of the Minister of Manpower of the Republic of Indonesia Number 2 of 2022 concerning Procedures and Requirements for Payment of Pension Plan Benefits, causes workers/laborers to lose their normative rights to work and a decent life in accordance with the objectives of labor law.The research method used is a normative legal research method, namely research on library materials which are basic data in science classified as secondary data. . Normative legal research serves to provide juridical arguments when there is a vacuum, ambiguity, and conflict of norms.Development in the field of manpower is basically in accordance with the objectives of the law, namely justice, order and benefit for the welfare of workers and their families. This is done because development in the field of manpower involves harmonious industrial relations between the government, employers, and workers. In the concept of a state of law, the provision of Pension Plan (JHT) benefits, the government in the field of manpower should provide legal protection for workers/laborers.